(untitled) (Web of Teachers: Inderscience Research, 2025)
LN-Jetronic is an injector fuel supply system used in modern cars, providing a more accurate and efficient fuel mixture by spraying the fuel into each cylinder via separate injectors. This system has a number of advantages over carburetor systems, including fuel economy, environmental friendliness, improved engine reliability and dynamic characteristics. The article analyzes in detail the structure, principle of operation, advantages and disadvantages of the LN-Jetronic system.